2011
DOI: 10.1111/j.1365-2125.2010.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP2C9*1/*13 on the pharmacokinetics and pharmacodynamics of meloxicam

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Meloxicam is a substrate for the CYP2C9 and CYP3A4 enzymes. • We have previously reported that the frequency of the CYP2C9*1/*13 genotype in the Korean population is 1.1%. WHAT THIS STUDY ADDS • The CYP2C9*1/*13 genotype is associated with decreased metabolism and increased pharmacodynamic effects of meloxicam. • This is the first report that evaluates the in vivo effects of the CYP2C9*13 allele on the pharmacokinetics and pharmacodynamics of CYP2C9 substrates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…4,5) These reports suggest that MEL undergoes enterohepatic circulation. Taking these findings into account, we are planning to investigate the process by which MEL is metabolized to 5-HMEL and 5-CMEL (e.g., glucuronide conjugate, CYP metabolism).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5) These reports suggest that MEL undergoes enterohepatic circulation. Taking these findings into account, we are planning to investigate the process by which MEL is metabolized to 5-HMEL and 5-CMEL (e.g., glucuronide conjugate, CYP metabolism).…”
Section: )mentioning
confidence: 99%
“…3) Studies of the human plasma concentration/time profile of MEL after a single oral administration indicate that the graph exhibits bimodal peaks. 4,5) These reports suggest that MEL undergoes enterohepatic circulation. Taking these findings into account, we are planning to investigate the process by which MEL is metabolized to 5-HMEL and 5-CMEL (e.g., glucuronide conjugate, CYP metabolism).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report, the genotype of CYP2C9*1/*13 was associated with decreased metabolism and increased pharmacodynamic effects of meloxicam in Korean subjects (Bae et al, 2011b). However, to the best of our knowledge, there are no reports concerning the relationship between CYP2C9*3 and pharmacodynamic effects of meloxicam in the Chinese population.…”
Section: Discussionmentioning
confidence: 88%
“…Thereafter, a series of investigations into the catalytic activity of CYP2C9*13 in vivo and in vitro were subsequently performed using tolbutamide, diclofenac, and lornoxicam as the probing substrates (Guo et al, 2005a(Guo et al, , 2005b. Moreover, genetic and clinic investigations in Korea had suggested that the presence of CYP2C9*13 allele statistically resulted in the poor metabolism of losartan and irbesartan after a single oral dose (Li et al, 2009;Choi et al, 2012), and also influenced the pharmacokinetics and pharmacodynamics of meloxicam (Bae et al, 2011). CYP2C9*16(T299A) and CYP2C9*19(Q454H) were discovered after studying 125 Asians from Singapore (Zhao et al, 2004).…”
Section: Introductionmentioning
confidence: 99%